DETERMINANTS OF SUSTAINABLE HEALTH DEVELOPMENT - Sri Sulistiowati and I Gusti Wayan Murjana Yasa (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2021)
Sustainable health development is a change that leads to a positive or better in the social, economic aspects whose implementation does not ignore the ecological or environmental and social aspects where all levels of society depend on environmental aspects. The successful implementation of sustainable health development requires integrated policies, planning and social learning processes. One of the government's efforts to encourage hospitals to prioritize service, safety and protection for the community is to require hospitals to carry out accreditation. Accreditation is an acknowledgment given to hospitals because they have strived to improve the quality of services on an ongoing basis. To ensure the realization of sustainable health development, it is very dependent on social capital, especially the community's ability to manage and overcome economic, social and environmental pressures. Communities that are endowed with wealth of social capital are in an advantageous position in implementing development programs. Thus, a healthy society will always be in a prosperous state, because it is still able to live productively. According to the previous explanation, it is known that government policies, social capital and public welfare affect the health of the community in a sustainable manner. This study tries to formulate the problem (1) How is the relationship between government policy and sustainable health development?; (2) What is the relationship between social capital and sustainable health development and (3) What is the relationship between welfare and sustainable health development?. This research is a literature review related to government policies in the health sector. Through the literature, this study attempts to analyze the relationship between government policy, social capital and welfare in relation to sustainable health. The conclusions of this study are (1) government policies affect sustainable health development?; (2) social capital affects sustainable health development and (3) welfare affects sustainable health development?